2000
DOI: 10.1021/ja001185c
|View full text |Cite
|
Sign up to set email alerts
|

CAS MCSCF/CAS MCQDPT2 Study of the Mechanism of Singlet Oxygen Addition to 1,3-Butadiene and Benzene

Abstract: The 1,4-cycloaddition reactions of the singlet (1Δg) oxygen with s-cis-1,3-butadiene and benzene, with the formation of 3,6-dihydro[1,2]dioxin and 2,3-dioxabicyclo[2.2.2]octa-5,7-diene, respectively, were studied by means of the CAS MCSCF/CAS MCQDPT2 ab initio method with the 6-31G* basis set. In the case of butadiene the reaction was found to be exoenergetic and the product was found to have C 2 symmetry, with the peroxide moiety in the gauche configuration. In the case of benzene the reaction was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 48 publications
4
102
1
Order By: Relevance
“…[15] The aim of this work was to study the reaction between pyridoxine and singlet oxygen. Pyridoxine has an aromatic six-membered ring, and as described by Bobrowski et al, [16] there are four principal types of oxygen-addition reactions to aromatic and unsaturated compounds: 1) 1,3-addition to a double bond connected to a hydrogen-carrying group, resulting in the formation of allylic hydroperoxides; Abstract: Singlet oxygen is known to cause oxidative stress in cells, leading to severe damage (e.g., lipid peroxidation, membrane degradation, mutagenic alterations to DNA, protein misfunctionality). Recently, pyridoxine has been discovered to be capable of quenching singlet oxygen, however, the mechanism of this reaction remains essentially unknown.…”
Section: Introductionmentioning
confidence: 93%
“…[15] The aim of this work was to study the reaction between pyridoxine and singlet oxygen. Pyridoxine has an aromatic six-membered ring, and as described by Bobrowski et al, [16] there are four principal types of oxygen-addition reactions to aromatic and unsaturated compounds: 1) 1,3-addition to a double bond connected to a hydrogen-carrying group, resulting in the formation of allylic hydroperoxides; Abstract: Singlet oxygen is known to cause oxidative stress in cells, leading to severe damage (e.g., lipid peroxidation, membrane degradation, mutagenic alterations to DNA, protein misfunctionality). Recently, pyridoxine has been discovered to be capable of quenching singlet oxygen, however, the mechanism of this reaction remains essentially unknown.…”
Section: Introductionmentioning
confidence: 93%
“…In our recent study of dioxygen 1,4-addition to cis-1,3-butadiene and benzene 23 we found a peroxacyclopenta-3-ene species with relatively low energy. These species are unlikely to occur on the reaction path of the formation of 1,4-peroxides, because a simpler reaction mode with a lower activation barrier is available.…”
Section: Introductionmentioning
confidence: 70%
“…Singlet oxygen is known to react with unsaturated compounds, including aromatic compounds, by several means (25). Addition of 1 O 2 to polycyclic aromatic compounds has been investigated in detail (26,27).…”
Section: Generation Mechanism Of Hydrogen Peroxidementioning
confidence: 99%
“…However, the addition of oxygen to benzene was generally thought to be unlikely reaction (27). Only the investigation of a mechanism of 1,4-oxygen addition to benzene in a one-step mechanism was reported by the study using CAS MCSCF/CAS MCQDPT2 (25). This mechanism was considered to be based on a reaction similar to that of ANT.…”
Section: Generation Mechanism Of Hydrogen Peroxidementioning
confidence: 99%